L'Afrique du Sud, l'Union européenne et la Convention de Lomé : du bilatéralisme au néo-régionalisme ? (Note) - Bach, Daniel (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1996)
Economic and financial relations between the European Union and « new » South Africa were characterized by a rapid process 0} normalization following the general elections of27 April 1994. Much more problematic has been the process of negotiating a long term relationship which should result in the implementation of a Eu-South Africa free trade area over a ten year transition period, and a qualified membership of South Africa in the Lome Convention. The analysis 0} current negotiations reveals how the parties' mutual concern for the World Trade Organisation principles is constantly tempered by their equally strong commitment to Systems of regional preferences. At a time when the future of the Lome Convention has become a matter of official discussion by the EU and the ACP states, the revival of regional integration programmes in Southern Africa confers to the negotiations between the EU and South Africa a special value. Indeed, they prefigure as a test on the capacity to integrate the realities of new trade regionalism in euro-African relations.